(untitled) (Journal of the College of Basic Education, 2023)
Due to what international trade involves in terms of the exchange of wealth and services and the operations it includesto transport goods and commodities from centers of production to consumption and investment markets; It took center stagein various international relations. The ease and diversity of communication led to the flourishing of international trade, in particularAfter the emergence of electronic commerce; This prompted the dealers in this field to search for means of trustAnd credit between them, and assumes this capacity in the documentary credit through his role in ensuring that the selleron the price of the goods sold. The essential element of the documentary credit system is the documents; And by trading it betweenBanks are committed to the seller-exporter, the “beneficiary”, who receives the price of his goods if he submits documents that conform to the conditionsAccreditation ; What increases his reassurance is the intervention of a banking institution. It is a full party that provides confidence to him;On the other hand, the buyer knows that the bank will not pay the consideration documents that are identical to what was stated in the letterAccreditation. If the documents are considered the cornerstone of the documentary credit system because of the material value they represent to the sellerand the buyer where we deal with the banks without the goods; Due to the prevalence of frauds in the tradeInternational, the buyer may not be reassured that the goods conform to the documents provided. And in this field he playsThe principle of exact conformity (5020) played an important role in examining documents to find out the truthIts compliance with the terms and conditions of the documentary credit.